Peran Kepala Sekolah Dalam Implementasi Kurikulum 2013 Di SMA Negeri 1 Brandan Barat - Adinda Nst, Syarifah, Syarifah Hidayani (Education Achievement: Journal of Science and Research, 2022)
This research is a type of qualitative research. The data collection procedure is by observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and data verification. Based on the results of this study, the role of the principal in implementing the 2013 curriculum at the State High School 1 Brandan Barat is very good, the principal has implemented, implemented, and carried out his leadersip in the role and function as an educational leader. Conducting monitoring to teachers regarding the implementation of the 2013 curriculum is expected to more often consult together on various obstacles or problems in the teaching and learning process in order to achieve current educational goals. The conclusion of this study is the role of the principal in implementaring the 2013 curriculum at the state high school 1 Brandan Barat, namely the principal applies monthly to teachers about the implementation of the 2013 curriculum in order to achieve current educational goals and become wise leaders.